PHYSIOLOGICAL BASIS OF IMPROVED YIELDS IN RAINFED COTTON UNDER HIGH DENSITY PLANTING SYSTEM - and V. GOURI SHANKAR, B. SANTHOSH, RAMESH THATIKUNTA, D. V. V. REDDY, S. A. HUSSAIN (The Journal of Research, PJTSAU, 2020)
Rainfed crop cultivation suffers from water stress situation. Physiological traits evaluation enables identification of gaps in realizing the improved productivity. Field experiment was conducted to find out suitable plant density and genotypes under rainfed conditions of Telangana during Kharif, 2015-2016 and Kharif 2016-2017 at college farm, College of Agriculture, Rajendrangar, PJTSAU. The results clearly indicated that lower plant density at 75 x 10 cm plant spacing performed better in terms of chlorophyll content, SPAD values and photosynthetic rate than higher plant densities at 65 x 10 cm and 45 x 10 cm. Osmolites production like proline was found higher under low plant density at 75 x 10 cm.